PENGEMBANGAN PENUNTUN PRAKTIKUM PEMBUATAN CENIL NANAS PADA SUB MATERI PERAN TUMBUHAN DI BIDANG EKONOMI - Weldan, U Nike; Daningsih, Entin; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the feasibility of laboratory work guidance for making pineapple cenil on the sub material of the plants role in economy and students? responses tolaboratory work guidance. The research was conducted by using Research and Development (R & D) method, consisting of six stages out of ten stages, namely potential and problem, data collection, product design, design validation, design revision and limited product trial. To know the feasibility of laboratory work guidance was evaluated by five validators consisting of two Biology education lecturers and three biology teachers from senior high school. Based on validation result of laboratory work guidance, there was 0,99 of CVI value in showed a valid criteria, in accordance to minimum value of Lawshe. There feasibility of all so followed by very high response (81,94%) by students? to laboratory work guidance for making pineapple cenil, so that laboratory work guidance suitable to be used as teaching materials on sub material of the plants role in economy.  Keyword: Feasibility, Laboratory Work Guidance, Pineapple Cenil, R&D Method, and Responses.